DEVELOPMENT OF PROBLEM BASED LEARNING MODULES ON ADDITIVES AND ADDICTIVE SUBSTANCES FOR ODD SEMESTER GRADE VIII SMP - indah rahmi lestari; Yurnetti Yurnetti (Universe, 2022)
This article base on the topic of research Development of Problem Based Learning modules on Additives and Addictive Substances for Grade 8th Junior High School the aims of the research is problem-based learning modules that can help students increase their interest in learning and learning independently in understanding additives and addictive substances, as well as investigating the validity of the type of research used is research and development or Research and Development by using ploomp development model consisting of three stages, namely preliminary research, prototiyng stage, and assessment phase. Research instruments used questionnaires (validity sheets) and one to one evaluation for learners. The module was validated by 3 validators from FMIPA UNP science education lecturers, this research was limited to one to one evaluation. The results of this study obtained a validity value of 70.31% with a valid category. Validity test on content feasibility aspect obtained a value of 81.25% with a very valid category, the linguistic aspect obtained a value of 58.33% with a fairly valid, the presentation aspect obtained a value of 66.67% with a valid category, and the aspect of chart obtained a value of 75.00% with a valid category. Thus, it can be concluded that the problem-based learning module based on additives and addictive substances developed meets valid criteria.